Penyutradaraan Sendratari Putir Busu dan Bawi Sandah - islamiyah islamiyah; Ichyatul Afrom; Marrisa Aulia Mayangsari (Tambuleng, 2025)
The creation of the dance-drama Putir Busu and Bawi Sandah aims to convey moral values while introducing the legend of the Dayak Ngaju people of Central Kalimantan, so that local culture and wisdom continue to thrive and be appreciated. This work is a new creation, conceptually arranged through the application of basic directing techniques to build dramatic unity, continuity of meaning, and character development through acting and movement. In addition to serving as a medium for cultural development, the work is also intended as a source of motivation and inspiration for other artists. The creative process is based on performing arts theories proposed by Ardini and Seten, including aesthetic, functional-structural, and symbolic theories, which are analyzed using a directing approach drawn from Riantriano’s research and character development concepts by Misnawati and Aswari. The dance-drama is performed by six actors and twelve dancers and is structured into three main scenes: prologue, conflict, and resolution. The performance employs 13 blocking patterns, 24 floor patterns, audio music accompaniment in MP3 format with a duration of 45 minutes and 20 seconds, as well as costumes and makeup reflecting Dayak Ngaju culture to reinforce cultural identity and inspire other artists.